2017
DOI: 10.1002/2017gl073559
|View full text |Cite
|
Sign up to set email alerts
|

Seasonally transported aerosol layers over southeast Atlantic are closer to underlying clouds than previously reported

Abstract: From June to October, low‐level clouds in the southeast (SE) Atlantic often underlie seasonal aerosol layers transported from African continent. Previously, the Cloud‐Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) 532 nm lidar observations have been used to estimate the relative vertical location of the above‐cloud aerosols (ACA) to the underlying clouds. Here we show new observations from NASA's Cloud‐Aerosol Transport System (CATS) lidar. Two seasons of CATS 1064 nm observations reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
74
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 48 publications
(68 reference statements)
2
74
3
Order By: Relevance
“…While it has been well documented that emission injection heights of fires require better characterization (Pfister et al, ), characterizing their vertical profiles over the WNAO is of great importance with regard to vertical heating rates and stability (Taubman et al, ) and interactions with clouds. Studies in other regions such as the southeastern Atlantic (Rajapakshe et al, ) and northeastern Pacific Ocean (Mardi et al, ) have looked at vertical characteristics such as the distance between plumes and cloud top heights. Similar work is warranted for the WNAO in pursuit of better understanding of regional ACI and subsequent effects on radiative forcing.…”
Section: Synthesis Of Results and Future Outlookmentioning
confidence: 99%
“…While it has been well documented that emission injection heights of fires require better characterization (Pfister et al, ), characterizing their vertical profiles over the WNAO is of great importance with regard to vertical heating rates and stability (Taubman et al, ) and interactions with clouds. Studies in other regions such as the southeastern Atlantic (Rajapakshe et al, ) and northeastern Pacific Ocean (Mardi et al, ) have looked at vertical characteristics such as the distance between plumes and cloud top heights. Similar work is warranted for the WNAO in pursuit of better understanding of regional ACI and subsequent effects on radiative forcing.…”
Section: Synthesis Of Results and Future Outlookmentioning
confidence: 99%
“…Transport System (CATS) (Yorks et al, 2014), shows that the CALIOP algorithm probably overestimates the base of the aerosol layer by 500 m (Rajapakshe et al, 2017). Deaconu et al (2017) showed that the CALIOP operational algorithm underestimates the AOT above clouds with a factor of 2 to 4 depending on the aerosol type, when compared to other methods dedicated for aerosol above cloud retrievals -the POLDER polarisation method (Waquet et al, 2009) and the CALIOP depolarisation ratio method DRM (Deaconu et al, 2017;Hu et al, 2007).…”
Section: Radiative Transfer Calculation and Synergy Caliop / Poldermentioning
confidence: 99%
“…However, contact between the base of smoke layers and the cloud-topped MBL is highly variable and difficult to constrain with satellite remote sensing (e.g. (Rajapakshe et al, 2017)). At Ascension Island (ASI, details below), there is frequently heavy smoke intrusion into the 10 MBL earlier in the burning season (June-August) than expected given the later (September-October) peak in aerosol optical depth (Zuidema et al, 2018).…”
mentioning
confidence: 99%